Comparative Study of Refraction between Wave Front-Based Refraction and Autorefraction without and with Cycloplegia in Children and Adolescents - Ana M Calvo-Maroto; Sara Llorente-González; Jaione Bezunartea-Bezunartea; Francisco Javier Hurtado-Ceña; Clara Berrozpe-Villabona; Valentina Bilbao-Malavé; David P Piñero; Jesús Barrio-Barrio; Sergio Recalde-Maestre (MDPI AG, 2022)
The main aim of this study was to compare refraction measurements with and without cycloplegia from two refractors devices, (TRK-2P autorefractometer (TRK-2P) and wavefront-based refraction Visionix 130 (VX130)) in children and adolescents. This descriptive observational study included 20 myopic eyes and 40 hyperopic eyes measured in two different Spanish hospitals. Cycloplegia was carried out by three drops of cyclopentolate hydrochloride 1% (Colircusí cycloplegic, Alcon Healthcare S.A., Barcelona). The mean age of the myopia group was 12.40 ± 3.48 years; for the hyperopia group, the mean age was 7.37 ± 2.47 years. In the myopia group, autorefraction and wavefront-based refraction did not show clinically significant differences in any components between with and without cycloplegia. The hyperopia group showed statistical and clinically significant differences in sphere and SE components between relaxed and non-relaxed states of accommodation, although the cylindrical components were not clinically different. In this study, we considered a value of ≥0.50D as a clinically significant difference in refraction. Therefore, both devices were capable of obtaining accurate refractions without cyclopegia in myopia children, although they did not avoid instrument myopia and accommodation involved in hyperopia children. Moreover, both refractometers could be useful for astigmatism monitoring in children without the need for cycloplegic drops.